Answer:
12
Step-by-step explanation:
Hello!
First of all you have to understand the order of operations.
PEMDAS
Parenthesis, Exponent, Multiplication/Divison, Addition, Subtraction.
From this you can see that we first have to deal with the exponent, then multiplication, then the addition.
So we get 2+9-(-1)
The 9 is from -3^2
2+9+1
11+1
12.
Hope this helps!
7*4=28
28+7m=49
49-28=21
7m=21
21/7=3
m=3
Answer:
30/pi cm
Step-by-step explanation:
2×pi×r =60
r = 60/2×pi =30/pi
(y + 1)^3 would just be dividing the two
If you want it completely simplified, then it’s the following:
(y + 1)(y + 1)(y + 1)
= y^2 + y + y + 1 (y + 1)
= y^2 + 2y + 1 (y + 1)
= y^3 + y^2 + 2y^2 + 2y + y + 1
= y^3 + 3y^2 + 3y + 1